2021
DOI: 10.1155/2021/7552546
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Probiotic Supplements for Psoriasis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Preclinical Trials

Abstract: Background. Patients with psoriasis need long-term medication to control their condition. Recent studies suggest that changing the intestinal flora may be a potential treatment. Methods. The databases were utilized to search the randomized controlled trials (RCTs) and preclinical trials about probiotic supplement in the treatment of psoriasis. The retrieval time is from the establishment of these databases to December 2020. RevMan5.3 was used for the risk assessment of bias and meta-analysis. This systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Multiple observations point to a promising role of probiotics and prebiotics 39 . Bile acid deficiency is reported to correlate with LPS translocation in the bloodstream and with psoriasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple observations point to a promising role of probiotics and prebiotics 39 . Bile acid deficiency is reported to correlate with LPS translocation in the bloodstream and with psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…A study of 800 psoriasis patients divided in two groups, treated for 1–8 weeks with oral bile acid (dehydrocholic acid) supplementation or with conventional treatment, showed that 57.9% of patients treated with bile acid had no relapse after 2 years, compared to 6% of patients from the other group 3 . Another RCT showed a reduction of the PASI of up to 75% in the probiotic group (vs. 41.9% in the placebo group) and a lower risk of relapse at a 6‐month follow up 39 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of clinical trials have explored the efficacy of probiotics ( Bifidobacterium infantis , Bifidobacterium longum , Bifidobacterium lactis , Enterococcus , Lactobacillus rhamnosus ) as the treatment of psoriasis with a modest improvement in the Psoriasis Area and Severity Index (PASI) [ 38 , 39 , 40 , 41 ]. Although a recent meta-analysis concluded that probiotics and the control group did not yield statistical significance ( p = 0.11) [ 42 ], possibly due to increased compliance in both groups after enrolment into clinical trials [ 37 , 43 ], probiotics demonstrated potentially positive effect with minimal adverse effects in psoriasis patients and warranted further studies.…”
Section: Introductionmentioning
confidence: 99%